Genomic insights into the emergence and spread of international clones of healthcare-, community- and livestock-associated meticillin-resistant Staphylococcus aureus: Blurring of the traditional definitions. (September 2016) - Bal, A.M.; Coombs, G.W.; Holden, M.T.G.; Lindsay, J.A.; Nimmo, G.R.; Tattevin, P.; Skov, R.L.
Highlights: The traditional epidemiology of MRSA is blurring. Genomic studies have helped in understanding the evolving epidemiology. Genomic tools are useful in relation to epidemiology and outbreaks. Abstract: The evolution of meticillin-resistant Staphylococcus aureus (MRSA) from meticillin-susceptible S. aureus has been a result of the accumulation of genetic elements under selection pressure from antibiotics. The traditional classification of MRSA into healthcare-associated MRSA (HA-MRSA) and community-associated MRSA (CA-MRSA) is no longer relevant as there is significant overlap of identical clones between these groups, with an increasing recognition of human infection caused by livestock-associated MRSA (LA-MRSA). Genomic studies have enabled us to model the epidemiology of MRSA along these lines. In this review, we discuss the clinical relevance of genomic studies, particularly whole-genome sequencing, in the investigation of outbreaks. We also discuss the blurring of each of the three epidemiological groups (HA-MRSA, CA-MRSA and LA-MRSA), demonstrating the limited relevance of this classification.